The Effect Of Addition Vitamin C On Feed With Different Doses Towards Growth And Survival Rate Of Giant Prawns (Macrobrachium rosenbergii) In the Recirculation System - Rahayu, Mita; M Tang, Usman; Mulyadi, Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on March 18th-May 1st, 2019 in the Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. The aimof this study is to determine the effect of the best dose of vitamin C addition of feed on the growth of giant prawns. The container of this research used a 60x40x40 cm 3 aquarium with 20 aquariums with a stocking density of 15 prawns/aquarium. This study used a Completely Randomized Design (CRD) with one factor of five treatment levels and four replications. Each treatment was given the addition of vitamin C as much as P0 (0 m g/kg), P1 (300 mg/kg), P2 (450 mg/kg), P3 (600 mg/kg), and P4 (750 mg/kg) feed. The results of the research showed that the best treatment was found in P3 (600 mg/kg) feed resulting in absolute weight growth of 1,26 g, specific growth rate of 7,72% and survival rate of 98,33%. Keywords : Macrobrachium rosenbergii, Vitamin C, Growth